2020
DOI: 10.3390/ijerph17082625
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Scientific Research on Healthcare Workers’ Occupational Health: A Bibliometric and Social Network Analysis

Abstract: In the last few years, the occupational health (OH) of healthcare workers (HCWs) has been shown increasing concern by both health departments and researchers. This study aims to provide academics with quantitative and qualitative analysis of healthcare workers’ occupational health (HCWs+OH) field in a joint way. Based on 402 papers published from 1992 to 2019, we adopted the approaches of bibliometric and social network analysis (SNA) to map and quantify publication years, research area distribution, internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 83 publications
0
23
0
3
Order By: Relevance
“…Some studies on healthcare workers' occupational health have been conducted regarding the prevention of infectious diseases, but they represent only 13% of a sample of 402 papers published between 1992 and 2019 on this matter. Besides, most of them are surveillance studies [23]. The authors have not identified any study addressing the use of SNA for the support of Occupational Health and Safety Services in the prevention of outbreaks within workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on healthcare workers' occupational health have been conducted regarding the prevention of infectious diseases, but they represent only 13% of a sample of 402 papers published between 1992 and 2019 on this matter. Besides, most of them are surveillance studies [23]. The authors have not identified any study addressing the use of SNA for the support of Occupational Health and Safety Services in the prevention of outbreaks within workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of databases, such as PubMed, Google Scholar, and Scopus, are able to meet the requirement for evaluating the global DDH research trends, the data for this study were collected from the Science Citation Index Expanded (SCI-Expanded) of Web of Science Core Collection (WOSCC) ( 19 , 24 ). Web of Science (WOS) is a large-scale, systematic, and multidisciplinary authoritative database, which contains numerous influential high-quality journals from countries worldwide ( 19 , 25 ). It is also one of the most frequently used databases in previous bibliometrics studies ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Web of Science (WOS) is a large-scale, systematic, and multidisciplinary authoritative database, which contains numerous influential high-quality journals from countries worldwide ( 19 , 25 ). It is also one of the most frequently used databases in previous bibliometrics studies ( 24 , 25 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VOSviewer is a friendly platform used to carry out these analyses; its creators provided documentation (manual and research articles) that allowed us to understand its functionality and use [52,64,68]. This program is used to study various scientific disciplines related to geology, for example, geotourism [69], fracking [70], and geological risks [71], as well as other areas of knowledge management [72], occupational health [73], education [74], etc. Publications on natural zeolites as environmental remedies began in the 1970s, representing 0.12% of papers; only two articles added eight citations, related to radioactive cobalt sorption [75] and the treatment of wastewater using clinoptilolite [76].…”
Section: Data Extraction and Analysismentioning
confidence: 99%